PENGARUH PEMBERIAN KOMBINASI PESTISIDA NABATI TERHADAP HASIL TANAMAN PADI (Oryza sativa L.) VARIETAS INPARA-3 SECARA SRI - Rainiyati . (Bioplantae, 2013)
This study aims to determine the effect of combinations of pesticides to pests and rice yield with System of Rice Intensification (SRI) in the tidal area. This Studies was conducted in Kuala Tungkal, especially at one of the farmers fields in Desa Bram ITAM Pembengis Kecamatan Tanjung Jabung Barat. This Studies activity was conducted from September to December 2013. The studies using randomized block design (RBD) with 6 treatments and each factor level in re-treatment 4 times with 5 plants sample. Based on the results of analysis of variance showed that administration of a combination treatment plant pesticides significantly affect plant height, number of tillers, number of productive tillers, grain permalai, production data, the percentage of pests, and no apparent effect on 1000 grain weight. In the tabulation of treatment combinations pesticide plant Leaf Extract Rhizome Extract Soursop + Jeringau get the highest production of 3.69 kg / plot treatment. Keywords: Rice, Nabati Pestisides, SRI, tidal land